ASUHAN KEPERAWATAN DENGAN TUBERCULOSIS (TBC) DALAM PENDEKATAN TEORI FLORENCE NIGHTINGALE (MODERN NURSING) - Hazrina, Fira Awanis; Irna Nursanti (CV. ADIBA ADISHA AMIRA, 2024)
The prevalence of TB worldwide has increased since 2018, where the number of TB cases was 6,116,536 cases, and in 2019 there were 10,400,000 cases of TB worldwide. Indonesia is ranked third highest after India and China. Based on this, there is an alternative care model theory to overcome the environment that can cause TB disease. Nightingale's conceptual model of nursing is one of them, Nightingale sees patients in the context of the entire environment consisting of the physical environment, psychological environment, and social environment. The purpose of this study is to improve health services in improving disease management conditions professionally and bringing individuals into optimal conditions for activities through fundamental initiatives that affect the environment. This study uses a method that is a nursing process approach based on the selected nursing theory. Techniques used in data collection are interviews, observation, physical examination and nursing care. The results showed that Florence's assessment focuses more on environmental conditions (physical, psychological and social environment). Focused on the individual's relationship with the environment, namely: lack of information about environmental hygiene, ventilation, garbage disposal, environmental pollution, social communication and others.